2020
DOI: 10.1088/1361-6579/ab8cb4
|View full text |Cite
|
Sign up to set email alerts
|

SmartProbe: a bioimpedance sensing system for head and neck cancer tissue detection

Abstract: Objectives: This study presents SmartProbe, an electrical bioimpedance (EBI) sensing system based on a concentric needle electrode (CNE). The system allows the use of commercial CNEs for accurate EBI measurement, and was specially developed for in-vivo real-time cancer detection. Approach: Considering the uncertainties in EBI measurements due to the CNE manufacturing tolerances, we propose a calibration method based on statistical learning. This is done by extracting the correlation between the measured impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Specifically, the instrument integrates a 3D-printed compliant mechanism to regulate the applied force on the tissue during the measurement of the tissue electrical bioimpedance (EBI). The EBI reflects the electrical characteristics of a tissue region and it has been demonstrated for identifying different tissue types (Faes et al , 1999) and even different pathological levels (Cheng et al , 2020; Baghbani et al , 2019). Since the diseased tissue has a looser cellular structure and contains more water as well as conductive ions (Naranjo-Hernández et al , 2019), its electrical conductivity is lower compared to the surrounding normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the instrument integrates a 3D-printed compliant mechanism to regulate the applied force on the tissue during the measurement of the tissue electrical bioimpedance (EBI). The EBI reflects the electrical characteristics of a tissue region and it has been demonstrated for identifying different tissue types (Faes et al , 1999) and even different pathological levels (Cheng et al , 2020; Baghbani et al , 2019). Since the diseased tissue has a looser cellular structure and contains more water as well as conductive ions (Naranjo-Hernández et al , 2019), its electrical conductivity is lower compared to the surrounding normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Bioimpedance is an emerging technique for monitoring anatomical structures and physiological processes. Recent studies demonstrated the use of bioimpedance techniques in different applications including cancer detection (Cheng et al, 2020;Mansouri et al, 2020;Tidy and Brown, 2021), tissue hydration (Lukaski et al, 2019), body composition (Vermeiren et al, 2021), vascular fluid flow (Anand et al, 2021) and bedside monitoring (Mulasi et al, 2015;Morais et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…8 It is featured with high accuracy, non-invasive, safe, and fast processing. Successful applications in cancer detection have been reported in Cheng et al, 9 Murdoch et al, 10 Pathiraja et al 11 In addition, the anatomic environment is usually complex, and thus it requires the probe of the SMI to be designed in a small size and possess sufficient dexterity. 12 Several previous studies have proposed different wrist designs based on conventional mechanical linkages such as ball joints, 13 universal joints, 14 cables and pulleys, 15,16 lead screws, 17,18 and serial chains in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is featured with high accuracy, non-invasive, safe, and fast processing. Successful applications in cancer detection have been reported in Cheng et al, 9 Murdoch et al, 10 Pathiraja et al 11…”
Section: Introductionmentioning
confidence: 99%